Comparison of Murine Sarcoma Viruses in Nonproducer and S(+)L(−)-Transformed Cells - Aaronson, Stuart A. (1972)
The biologic properties of murine sarcoma viruses in nonproducer and S(+)L(−) cells were compared. Each virus was found to be genetically stable through at least two cycles of rescue and transmission to new cells. There was no evidence for production of a defective murine leukemia virus by S(+)L(−) cells. The results are most consistent with the hypothesis that the sarcoma genome in S(+)L(−) cells contains information for replication functions which the virus in nonproducer cells either lacks or does not express.